The Role of Interspecific Hybridisation in Adaptation and Speciation: Insights From Studies in Senecio - Wong, Edgar L. Y.; Hiscock, Simon J.; Filatov, Dmitry A. (Frontiers in Plant Science, 2022)
Hybridisation is well documented in many species, especially plants. Although hybrid populations might be short-lived and do not evolve into new lineages, hybridisaiton could lead to evolutionary novelty, promoting adaptation and speciation. The genus Senecio (Asteraceae) has been actively used to unravel the role of hybridisation in adaptation and speciation. In this article we first briefly describe the process of hybridisation and the state of hybridisation research over the years. We then discuss various roles of hybridisation in plant adaptation and speciation illustrated with examples from different Senecio species, but also mention other groups of organisms whenever necessary. In particular, we focus on the genomic and transcriptomic consequences of hybridisation, as well as the ecological and physiological aspects from the hybrids’ point of view. Overall, this article aims to showcase the roles of hybridisation in speciation and adaptation, and the research potential of Senecio, which is part of the ecologically and economically important family, Asteraceae.